An Analysis of Students’ Ability in Using Punctuation Marks in Descriptive Paragraph Writing - Fiber Yun Ginting (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Punctuation is one of the most important aspects of written English, and yet it is one that is taken the most lightly. It is, in fact, this feature of writing that gives meaning to the written words much like pauses and changes in tones of the voice when speaking. This study also has objective to explore the ability of students in placing punctuation marks in descriptve paragraph.The writer used descriptive qualitative research to give description systematically and factually about facts of a certain population.This research only describes how the students’ ability in using punctuation mark in writing descriptive paragraph.The students’ ability in using punctuation marks in descriptive writing was categorized into low,It can be classified that only 1 (one) students or 2% was categorized into excellent who got score 80 from the total students were 53 students, and 10 (ten) students or 10% were categorized into Good, 17 (seventeen) students or 32% were categorized into fair, 13 (thirteen) students or 24.5% were categorized into Low, and 12 (twelve) students or 22.5% were categorized into Failed.